1997
DOI: 10.1093/emboj/16.8.1832
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane domain-dependent sorting of proteins to the ER and plasma membrane in yeast

Abstract: organelles: the plasma membrane (Sso1p and the closely MRC Laboratory of Molecular Biology, Hills Road, related Sso2p), an endosomal/pre-vacuolar compartment Cambridge CB2 2QH, UK (Pep12p), the cis-Golgi (Sed5p) and the endoplasmic 1 Corresponding author reticulum (ER) (Ufe1p) (Hardwick and Pelham, 1992;Aalto et al., 1993;Becherer et al., 1996; Lewis and Sorting of membrane proteins between compartments Pelham, 1996). t-SNAREs in different compartments are of the secretory pathway is mediated in part by their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
165
1
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(181 citation statements)
references
References 38 publications
14
165
1
1
Order By: Relevance
“…As a general rule, the length of the TMDs increases from inside to outside, if one moves along the secretory pathway. The shortest TMDs are observed in ER proteins (ϳ16 aa) and the longest in plasma membrane proteins (ϳ25 aa) (Rayner and Pelham, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…As a general rule, the length of the TMDs increases from inside to outside, if one moves along the secretory pathway. The shortest TMDs are observed in ER proteins (ϳ16 aa) and the longest in plasma membrane proteins (ϳ25 aa) (Rayner and Pelham, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In studies in yeast (see Rayner and Pelham, 1997) and more recently in plants (Brandizzi et al, 2002), the length of the TM helix has been shown to play a major role in protein sorting because the helix needs to be at least 23 amino acids to span and to permit sorting to the PM. The predicted TM helices of MtLecRK1;1 and MtLecRK7;2 are 23 amino acids in length, thus fulfilling this sorting requirement.…”
Section: Discussionmentioning
confidence: 99%
“…This allowed the initial sorting of the altered proteins into the exocytic or vacuolar pathway to be determined without the complication of subsequent endocytosis. It has previously been shown that the destination of membrane proteins leaving the yeast Golgi is affected by the length and composition of their TMDs (Rayner and Pelham, 1997). Snc1p has a TMD of 20 residues, shorter than is typical for plasma membrane proteins in yeast (Munro, personal communication), and to investigate its importance for targeting we prepared a number of chimeras with altered TMDs.…”
Section: Sorting Of Gfp-snc1p During Exit From the Golgimentioning
confidence: 99%